Implementation of Green Marketing Strategies and Green Purchase Behavior as Efforts to Strengthen the Competitiveness of MSMEs in Indonesia - Bestari, Dinda Kayani Putri; Butarbutar, DJ Anderson (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The contribution of UMKM business actors is considered quite significant for the development of the economic structure, however, the UMKM sector players must still manage their strategies so that this contribution can continue to grow. To achieve sustainability and continue to make a positive contribution, MSMEs must have a business strategy and competitive power that are relevant to market conditions. The discussion about environmentally friendly products is increasingly being discussed. The high people's willingness to buy environmentally friendly products illustrates that more and more consumers are starting to become aware of environmental conservation and minimize environmental pollution due to the consumption of certain products. This is considered as an opportunity, companies try to respond positively and encourage companies to do innovative things by introducing new business strategies known as green marketing strategies. Researchers will try to see how green marketing strategies influence the trust of green customers, then how green marketing strategies and green customer trust affect green purchase intention and green purchase behavior in the MSME sector, especially in the type of handmade environmentally friendly Indonesian products. This study used the PLS (Partial Least Square) data analysis method using the SmartPLS version 3. The respondents in this study were 350 respondents spread across several regions of Indonesia. The technique of distributing questionnaires used the snowball sampling method. The research result states that green marketing strategies, green customers, and green purchase intention have a very big influence in shaping the behavior of purchasing environmentally friendly products for green consumers.